2015
DOI: 10.1016/j.hrthm.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Importance of nonpulmonary vein foci in catheter ablation for paroxysmal atrial fibrillation

Abstract: Success rates can be improved for PAF ablation if non-PV foci are detected and eliminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 18 publications
2
92
3
2
Order By: Relevance
“…17, 19 We previously reported that the success rate of PAF ablation can be improved if all non-PV foci are detected and eliminated, although the mapping of all non-PV foci is technically challenging, even with the use of multiple procedures. 18 In the present study, at least 9.3% of patients had multiple non-PV foci in the SSS group, indicating that efforts to identify and ablate non-PV foci in patients with SSS, despite the presence of multiple non-PV foci or low reproducibility, may reduce the risk of subsequent AF recurrence.…”
Section: Discussionmentioning
confidence: 48%
“…17, 19 We previously reported that the success rate of PAF ablation can be improved if all non-PV foci are detected and eliminated, although the mapping of all non-PV foci is technically challenging, even with the use of multiple procedures. 18 In the present study, at least 9.3% of patients had multiple non-PV foci in the SSS group, indicating that efforts to identify and ablate non-PV foci in patients with SSS, despite the presence of multiple non-PV foci or low reproducibility, may reduce the risk of subsequent AF recurrence.…”
Section: Discussionmentioning
confidence: 48%
“…42 Catheter ablation of these non-PV triggers added to PV isolation was shown to improve the outcome in paroxysmal AF. 43 Localization of non-PV AF triggers, however, is still challenging, particularly when multifocal non-PV triggers are targeted. Santangeli et al reported that non-PV triggers were elicited in 11% of AF patients and these triggers were typically clustered in discrete anatomic regions such as the inferior mitral annulus, posterior LA, interatrial septum, particularly at the fossa ovalis/limbus region, crista terminalis, Eustachian ridge, coronary sinus (CS), and the SVC (Figure 5).…”
Section: Ablation Of Non-pv Triggersmentioning
confidence: 99%
“…[69][70][71][72][73][74][81][82][83] Non-PV triggerablation protocols generally involve burst-pacing protocols with isoproterenol infusion to induce the triggers, followed by mapping patients with long-standing persistent AF). 33,84,85 This incidence seems to increase with age, worse atrial substrate and in the presence of cardiomyopathy.…”
Section: Clinical Valuementioning
confidence: 99%
“…Most studies considered repetitive premature atrial contraction as the target for ablation. 9,33,[81][82][83][84][85][86][87] Several repetitive premature atrial contractions, however, will never induce AF. As such, an increased success rate has been achieved when targeting only the premature atrial contractions that induce AF.…”
Section: Clinical Valuementioning
confidence: 99%